2010
DOI: 10.1371/journal.pone.0015081
|View full text |Cite
|
Sign up to set email alerts
|

At What Stage of Neural Processing Does Cocaine Act to Boost Pursuit of Rewards?

Abstract: Dopamine-containing neurons have been implicated in reward and decision making. One element of the supporting evidence is that cocaine, like other drugs that increase dopaminergic neurotransmission, powerfully potentiates reward seeking. We analyze this phenomenon from a novel perspective, introducing a new conceptual framework and new methodology for determining the stage(s) of neural processing at which drugs, lesions and physiological manipulations act to influence reward-seeking behavior. Cocaine strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
225
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(235 citation statements)
references
References 93 publications
(156 reference statements)
6
225
2
Order By: Relevance
“…In support to this possibility, Yuan et al, (2013) recently identified GluN3A mediated current in VM DA neurons and showed that GluN3A-containing NMDARs mediate DA neurons plasticity induced by cocaine reward. Alternative hypotheses are that the reduction in GluN2A receptor was not sufficient to modify the excitatory drive of glutamate or that the behavioral change was not reliably detectable by the curve-shift paradigm and some other more sensitive paradigm, like the reward-mountain paradigm (Hernandez et al, 2010) would be necessary to detect such changes. The likelihood of these hypotheses, however, is very low given that a comparable downregulation in the GluN1 receptor produced a significant reduction in reward pursuit that was readily detectable by the behavioral paradigm that we used.…”
Section: Discussionmentioning
confidence: 99%
“…In support to this possibility, Yuan et al, (2013) recently identified GluN3A mediated current in VM DA neurons and showed that GluN3A-containing NMDARs mediate DA neurons plasticity induced by cocaine reward. Alternative hypotheses are that the reduction in GluN2A receptor was not sufficient to modify the excitatory drive of glutamate or that the behavioral change was not reliably detectable by the curve-shift paradigm and some other more sensitive paradigm, like the reward-mountain paradigm (Hernandez et al, 2010) would be necessary to detect such changes. The likelihood of these hypotheses, however, is very low given that a comparable downregulation in the GluN1 receptor produced a significant reduction in reward pursuit that was readily detectable by the behavioral paradigm that we used.…”
Section: Discussionmentioning
confidence: 99%
“…As a neuromodulator, DA cannot produce significant synaptic currents directly to produce firing. But it can change the gain of other signals, in this case the reference signal for the rate of change, which is sent via the glutamatergic projections to the striatum [55]. Reduced DA may therefore result in a reduced velocity reference signal.…”
Section: The Role Of Dopamine In the Basal Gangliamentioning
confidence: 99%
“…ICSS is typically measured in the curve-shift (Edmonds and Gallistel, 1974;Edmonds and Gallistel, 1977;Miliaressis et al, 1986) or progressive-ratio (Hodos, 1961) paradigm. It has been demonstrated recently (Arvanitogiannis and Shizgal, 2008;Hernandez et al, 2010;Trujillo-Pisanty et al, 2011) that neither method provides sufficient isolation of the different processes underlying reward seeking to distinguish between competing hypotheses concerning the variables to which dopamine neurons contribute, which include the sensitivity and gain of brain reward circuitry (Hernandez et al, 2010) and subjective effort cost (Salamone et al, 2005;Niv et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The ambiguity inherent in curve-shift and progressive-ratio measures is reduced by measuring ICSS as a function of both the strength and cost of reward (Arvanitogiannis and Shizgal, 2008;Hernandez et al, 2010). This method, which produces a threedimensional (3D) structure called the "reward mountain," can distinguish between changes in the sensitivity of the reward circuitry and changes in a diverse set of variables that includes reward-circuit gain, subjective effort cost, and the value of alternate activities, such as grooming, exploring, and resting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation